The interplay of economic reforms and monetary policy: the case of the euro area - Francesco Drudi; Alain Durré; Francesco Paolo Mongelli (European Central Bank (ECB), 2012)
The world has been struck by a mutating systemic financial crisis that is unprecedented in terms of financial losses and fiscal costs, geographic reach, and speed and synchronisation. The crisis from August 2007 to date can be divided into three main phases: the financial turmoil from August 2007 to the collapse of Lehman Brothers; the global financial crisis from September 2008 until spring 2010; and the euro area sovereign debt crisis from spring 2010 to the current period. While each phase has brought significant challenges, the current sovereign debt crisis has been the most critical stage for the euro area. It has brought unprecedented challenges for the monetary union and triggered extraordinary adjustments in both monetary policy and institutional arrangements at the euro area level. The purpose of this article is to outline the features of each crisis phase, to describe the actions taken by the European Central Bank (ECB) during each phase and to explain the rationale for such measures. It also discusses the need to strengthen further the economic union in order to guarantee the sustainability of the monetary union of the euro area. In this respect, it is argued that the recent institutional adjustments made at the EU level would have been necessary independently of the financial crisis.
Keywords: D78; E52; E58; G01; H12; 330; Eurosystem; financial and institutional reforms; financial crisis; Monetary policy decision-making